Vocabulary lists and activities for the preK-2 classroom : integrating vocabulary, children's literature, and think-alouds to enhance literacy - Israel, Susan E. (Thousand Oaks, Calif. : Corwin Press, 2009)
A collection of vocabulary lists and activities for the prekindergarten through second-grade classroom, designed to help develop oral language and reading and writing skills.
Back to school -- People I know -- Kindness counts -- My favorites -- Classroom jobs -- Understanding directions -- School themes -- Parent volunteers -- Witty words we know from A-Z -- Words we use when we go places -- Dr. Seuss fun -- Name games -- My word wall -- ABC books resource list -- What to say instead of "sound it out" -- Words with r-controlled vowels -- The "H" brothers -- Cow words -- What are you thinking? -- Books with lessons -- We are special -- Wired words -- "Words I know" web -- Nonfiction for everyone -- Cookbook fun -- Bugs and brains -- Factual fun -- Cultural curiosity -- Happy birthday -- Celebrating the 100th day -- Holidays -- Seasonal fun -- Literacy day -- Writer's world words -- Ideas for writing -- Writing prompts -- Creative writing connections -- Vocabulary word list from Israel and Fry's research -- Writing responses -- Books to help children with writing.
Includes bibliographical references and index.
Professional
Vocabulary word list from Israel and Fry's research -- Writing responses --
Keywords: English language -- Composition and exercises -- Study and teaching (Early childhood); Language arts (Early childhood); Vocabulary -- Study and teaching (Early childhood) -- Activity programs; English language -- Composition and exercises -- Study and teaching; Language arts; Vocabulary -- Study and teaching